The Effect of Combining Rig Joint and Blendshape Methods on Faces to Increase Efficiency in 3D Animation - Imam Ainudin Pirmansah (Gayaku Publisher, 2024)
Facial animation is an important aspect in 3D character animation, because emotional delivery involves more animation on the face, such as how to express and dialogue between characters. Therefore animators must have experience in facial expressions, how to understand anatomy, and how facial muscles react and connect with each other. Facial Action Coding System or (FACS) is one of the reference systems in this study. This study uses a combination of approaches between joint-based matches and mixed-based rigging (blendshape) models. The face animation parameters based on 6 common expressions are; smile, disgust, anger, fear, sadness, and shock.This research uses experimental trials involving 3 parameters in testing, namely rigging efficiency, memory usage efficiency, and time estimation efficiency when rendering